Reporting environmental information in annual reports : Analysis of legal requirements in the Nordic countries (Copenhagen : Nordic Council of Ministers, 2008)
This report aims at exploring legal requirements to include environmental information in annual reports as an important driver for companies' focus on environmental matters and to identify ways of improving companies' reporting of environmental information in their annual reports. All Nordic countries, except Iceland, have legal requirements to disclose environmental information in the annual report. Supplementary non-legally required reports such as environmental reports and sustainability reports are not included in this study. The data for the report were collected from Ultimo 2006 through June 2007. This Report has been prepared for the NMR-IPP Group under the Nordic Council of Ministers by PricewaterhouseCoopers.